Determinants of change in stroke-specific quality of life after distributed constraint-induced therapy - Yan Hua Huang (2018)
OBJECTIVE. We identified the predictive factors of change in quality of life (QOL) after a distributed form of constraint-induced therapy (dCIT) among stroke survivors. METHOD. Seventy-four participants were treated with dCIT. We identified eight potential determinants of change: age, gender, side of lesion, time since stroke, cognitive status, motor impairment of the upper extremity, activities of daily living (ADLs), and instrumental ADLs (IADLs). The Stroke-Specific Quality of Life Scale (SS-QOL) was used to assess QOL. RESULTS. Right-sided lesion and onset > 17 mo earlier determined greater improvement in the SS-QOL Energy domain. Onset > 10 mo earlier, poorer IADL performance, and age > 68 yr predicted improvement in the Family Role, Mobility, and Mood domains, respectively. CONCLUSION. Side of lesion, time since stroke, IADL performance, and age were the most important determinants of QOL in patients receiving stroke motor rehabilitation.